Multiple, ligand-dependent routes from the active site of cytochrome P450 2C9 - Cojocaru, Vlad; Winn, Peter; Wade, Rebecca C. (Current drug metabolism, 2012)
The active site of liver-specific, drug-metabolizing cytochrome P450 (CYP) monooxygenases is deeply buried in the protein and is connected to the protein surface through multiple tunnels, many of which were found open in different CYP crystal structures. It has been shown that different tunnels could serve as ligand passage routes in different CYPs. However, it is not understood whether one CYP uses multiple routes for substrate access and product release and whether these routes depend on ligand properties. From 300 ns of molecular dynamics simulations of CYP2C9, the second most abundant CYP in the human liver we found four main ligand exit routes, the occurrence of each depending on the ligand type and the conformation of the F-G loop, which is likely to be affected by the CYP-membrane interaction. A non-helical F-G loop favored exit towards the putative membrane-embedded region. Important protein features that direct ligand exit include aromatic residues that divide the active site and whose motions control access to two pathways. The ligands interacted with positively charged residues on the protein surface through hydrogen bonds that appear to select for acidic substrates. The observation of multiple, ligand-dependent routes in a CYP aids understanding of how CYP mutations affect drug metabolism and provides new possibilities for CYP inhibition.